The Combination of Sensor Digital Kariasa Early Detection Prototype and Health Education for Self-Management in Preventing Recurrent Ischemic Stroke - I Made Kariasa SKp., MM., MKep., SpKep., MB; Elly Nurachmah SKp., MApp.Sc., DNSc; S. Setyowati SKp., MAppSc., PhD; Raldi Artono Koestoer DEA (SAGE Publishing, 2022)
Introduction Recurrent stroke is one of the concerns that not only causes functional disability but also economic and psychosocial problems. Self-management is one of the indicators to predict recurrent stroke. Field observations indicate there is currently no tool to increase the survivors' self-awareness. Objective The study aimed to investigate if an early detection tool and health education can improve patient self-awareness toward self-management in ischemic stroke patients in order to prevent recurrent ischemic stroke. Methods This study consisted of two stages. In the first stage, the study used research and development methods to develop a digital sensor tool named Sensor Digital Kariasa (SenDiKa). In the second stage, the study used a quasi-experimental design with a pretest-posttest control group involving 44 postischemic stroke patients who were selected by using consecutive sampling. The subjects were divided into intervention and control groups, and the length of the intervention was 12 weeks. Results This study found a significant difference between the two groups ( P  < .001). The intervention group who used the early detection tool and received health education showed better self-management compared to the control group. The use of SenDiKa early detection prototype and health education for self-management was perceived useful and gave positive effect to the improvement of self-management in poststroke patients to prevent recurrent stroke. Conclusion The combination of SenDiKa early detection prototype and health education for self-management can be used for patients to identify the major risk factors of recurrent stroke, such as blood pressure, blood sugar, and cholesterol.